The Correlation between Stature and Humerus Length in Adult Tamil Women and Men in Medan, Indonesia - Fernando; Saharnauli Janna Verawaty Simorangkir; Ade Pryta Romanauli Simaremare (Majalah Biomorfologi, 2026)
Background: The humerus is one of the most reliable long bones for estimating stature in forensic identification. The Tamil community represents a significant immigrant population in Medan, Indonesia. However, no previous study has evaluated stature estimation from humeral length in this population. such data are essential for forensic identification. Objective: To assess the relationship between humerus length and stature and to develop linear regression equations for estimating stature among Tamil adults in Medan. Materials and Methods: The authors conducted a descriptive cross-sectional study from September to October 2024 at Bodhi Gaya Vihara, Medan. The sample consisted of 100 Tamil adults (50 men and 50 women) who fulfilled the inclusion and exclusion criteria. Stature was measured using a microtoise, while humerus length was measured with a vernier caliper (Tricle, 0–600 mm, Shanghai, China). Correlation and simple linear regression analyses were performed. Results: We observed significant positive correlations between humerus length and stature. In men, the correlation coefficients were r = 0.660 (p < 0.001) for right humerus and r = 0.718 (p < 0.001) for left humerus. In women, the correlations were r = 0.574 (p = 0.001) and r = 0.546 (p = 0.001) for right and left humeri, respectively. Simple linear regression equations were generated, demonstrating that stature can be estimated from humerus length. Conclusion: Humerus length was significantly associated with stature in Tamil adult men and women. The derived regression equations in this study may be used to estimate stature in this population for forensic purposes.